RISK FACTORS FOR OPERATIVE WOUND INFECTION IN PATIENTS UNDERGOING PEDIATRIC CARDIAC SURGERY - Labarba , Arthur Azeredo; Cavalcante , Luiz Felipe Antônio Vieira; Pedreira , Jordana Clara Gomes; Filho , Edward Rodrigues de Oliveira; Souza , Cristiana Daniela de; Junqueira , Julia Ferreira; Barbosa , Érico Roberto; Sousa , Ana Carolina Dutra de; Pereira , Héllida Patrícia Oliveira Camilo; Obeid , Gabriel Raizama; Pitanga , Anthony Yuri Viana; Gomes, Charles Correa (Brazilian Journal of Implantology and Health Sciences, 2024)
Surgical wound infection is a significant complication in patients undergoing pediatric cardiac surgery, which can compromise the postoperative recovery process and increase morbidity. Several risk factors are associated with this condition, including patient characteristics, type of surgical procedure, hospital environment, and postoperative care practices. Understanding these factors is crucial to developing effective prevention strategies and optimizing clinical outcomes in this vulnerable population. Objective: To analyze and synthesize the available evidence on the risk factors for surgical wound infection in patients undergoing pediatric cardiac surgery. The aim is to identify patterns and gaps in the literature, contributing to a more comprehensive understanding of the elements that influence the occurrence of this specific complication. Methodology: The review was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The PubMed, Scielo and Web of Science databases were consulted to identify studies published in the last 10 years, using the descriptors "pediatric heart surgery", "operative wound infection", "risk factors", "children" and "prevention ". Three inclusion criteria were established, considering original studies that addressed risk factors in pediatric cardiac surgery, while three exclusion criteria were applied to filter articles that did not meet the specific objectives of the review. Results: Results revealed a variety of risk factors, including patient age, length of surgery, presence of comorbidities, and infection control practices. The review highlighted the importance of specific preventive strategies for the pediatric population undergoing cardiac procedures. Conclusion: This systematic review provides a comprehensive overview of risk factors for surgical wound infection in pediatric cardiac surgery, emphasizing the need for personalized prevention approaches. The conclusions highlight the importance of targeting preventive interventions, adapting them to the unique characteristics of this population, aiming to improve clinical results and reduce the incidence of postoperative infections.